Impementasi Metode Penemuan Terbimbing Guna Meningkatan Kepercayaan Diri Siswa Dalam Belajar Matematika - Nurul Husnah Mustika Sari (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2020)
This research aims to increase student’s self confidence in XI SMA in mathematics learning by using guided discovery learning. This research is an action research. It is a colaboated research by researcher and teacher. This reasearch used Kemmis & Mc. Taggart model. The subject of this research is students of XI SMA. The instruments that used in this research are observation sheets, questionnaire, and written test. Form this research, it is shown that guided discovery learning that used worksheet to discover concept, can be used to increase student’s self confidence. It can be seen from the increase in the percentage of student’s who have very high self confidence categories and the increase of student’s self confidence mean after two cycle.